Fucoxanthin, a Marine Xanthophyll Isolated From Conticribra weissflogii ND-8: Preventive Anti-Inflammatory Effect in a Mouse Model of Sepsis - Su, Jingqian; Guo, Kai; Huang, Min; Liu, Yixuan; Zhang, Jie; Sun, Lijun; Li, Daliang; Pang, Ka-Lai; Wang, Guangce; Chen, Long; Liu, Zhiyu; Chen, Youqiang; et al. (Frontiers in Pharmacology, 2019)
Background: Fucoxanthin (FX), a xanthophyll pigment which occurs in marine brown algae with remarkable biological properties, has been proven to be safe for consumption by animals. Although FX has various pharmacological effects including anti-inflammatory, anti-tumor, anti-obesity, antioxidant, anti-diabetic, anti-malarial, and anti-lipid, in vivo protective effect against sepsis has not been reported. In this study, we aimed at evaluation the efficacy of the FX in a model of sepsis mouse. Methods: FX was successfully isolated from Conticribra weissflogii ND-8 for the first time. The FX was identified by thin-layer chromatography (TLC), high-performance liquid chromatography-mass spectrometry (HPLC-MS), and nuclear magnetic resonance (NMR). Animals were randomly divided into 9 groups, including Sham group (mouse received an intraperitoneal injection of normal saline 1.0 mL/kg), FX-treated (0.1–10.0 mg/kg), Lipopolysaccharide (LPS)-treated (20 mg/kg), FX+LPS-treated (0.1–10.0 mg/kg and 20 mg/kg, respectively), and urinastatin groups (104 U/kg). Nuclear factor (NF)-κB activation could be potential treatment for sepsis. Inflammasome components were determined by western-blotting. IL-6, IL-1β, TNF-α production, and NF-κB activation were evaluated by ELISA and immunofluorescent staining in vitro. Results: FX was found to decrease the expression of inflammatory cytokines including IL-6, IL-1β, and TNF-α, in the LPS-induced sepsis mouse model. Meanwhile, FX significantly- inhibits phosphorylation of the NF-κB signaling pathway induced by LPS at the cellular level and reduces the nuclear translocation of NF-κB. The IC50 for suppressing the expression of NF-κB was 11.08 ± 0.78 μM in the THP1-Lucia™ NF-κB cells. Furthermore, FX also inhibits the expression of inflammatory factors in a dose-dependent manner with the IC50 of inhibition of IL-6 production was 2.19 ± 0.70 μM in Raw267.4 macrophage cells. It is likely that the molecules with the ability of targeting NF-κB activation and inflammasome assembly, such as fucoxanthin, are interesting subjects to be used for treating sepsis.